Karakteristik Genetik Populasi Kuno Pulau Bali: Sanur dan Gilimanuk - Rusyad Adi Suryanto; Toetik Koesbardiati; Delita Bayu Murti; Ahmad Yudianto; Anak Agung Putu Santiasa Putra (Berkala Arkeologi Sangkhakala, 2014)
AbstractThe study of ancient human migration and peopling in Indonesia still raises debate until now, both from the perspective of biological anthropology, human genetics or archaeological. The debate was always open space again to do some research about that. We concentrated with samples of ancient Bali, the findings of human remains from Gilimanuk (Melaya, Jembrana) and Semawang (Sanur, Denpasar). Relatively, Bali is an island located in the centre of Indonesian Archipelago, which may represent a major pathway of human migration and distribution according to the outer arc islands. The research aimed to describe human genetic variation of the two archeological sites of ancient Bali. Based locus short tandem repeats (STR) combined DNA index system (CODIS), which CSF1PO, TH01 and TP0X, the research took a sample of six individual human ancient Bali, which includes each of the three individual from Semawang and Gilimanuk site. The process of genetic research has been done at the Institute of Tropical Disease Laboratory of Human Genetics, Airlangga University. Semawang and Gilimanuk derived from different populations based on the analysis of its CTT loci visualization. The results with reference to all possible aspects of archaeology and biological anthropology further enrich the wealth of knowledge about human migration events in Indonesia around the Neolithic period, the early times of increasingly massive mongoloid migrations to the Archipelago region. The results also further strengthen the results of previous genetic studies of Bali population. Balinese has undergone a genetic mixture of various immigrant populations since the Neolithic period.AbstrakPenelitian migrasi dan penghunian manusia kuno di Indonesia masih memunculkan perdebatan sampai kini, baik dari perspektif antropologi biologis, genetika manusia atau arkeologis. Perdebatan itu selalu membuka ruang lagi untuk melakukan penelitian perihal itu. Kali ini kami berkonsentrasi dengan sampel Bali Kuno, yakni temuan sisa-sisa manusia dari Gilimanuk (Melaya, Jembrana) dan Semawang (Sanur, Denpasar). Bali merupakan pulau yang relatif terletak di tengah gugusan kepulauan Indonesia, di mana dapat mewakili jalur besar migrasi dan persebaran manusia seturut rute pulau-pulau busur luarnya. Penelitian ini bertujuan untuk mendeskripsikan variasi genetik manusia kuno dari dua situs arkeologis Bali itu. Berdasarkan lokus short tandem repeats (STR) combined DNA index system (CODIS), yakni CSF1PO, TH01 dan TP0X, penelitian ini mengambil sampel enam individu manusia Bali Kuno, yang meliputi masing-masing tiga individu Semawang dan Gilimanuk. Proses penelitian genetik itu telah dikerjakan di Laboratory of Human Genetics, Institute of Tropical Disease, Universitas Airlangga. Sampel Semawang dan Gilimanuk berasal dari populasi yang berbeda berdasarkan analisis visualisasi lokus CTT-nya. Hasil penelitian ini dengan merujuk semua kemungkinan aspek arkeologis dan antropologi biologisnya makin memperkaya khazanah pengetahuan tentang peristiwa migrasi manusia di Indonesia sekitar masa Neolitik, yang menjadi masa awal makin masifnya migrasi Mongoloid ke kawasan Nusantara. Hasil penelitian ini juga makin menguatkan hasil-hasil penelitian genetika populasi Bali sebelumnya bahwa populasi Bali dari sejak Neolitik sampai sekitar masa yang lebih resen diturunkan oleh banyak leluhur atau banyak sumber gen. Penduduk Bali telah mengalami percampuran genetik dari berbagai populasi pendatang sejak Neolitik atau awal Tarikh Masehi.